Weakly-normal basis vector fields in RKHS with an application to shape Newton methods - Paganini, A; Sturm, K (Society for Industrial and Applied Mathematics, 2019)
We construct a space of vector fields that are normal to differentiable curves in the plane. Its basis functions are defined via saddle point variational problems in reproducing kernel Hilbert spaces (RKHSs). First, we study the properties of these basis vector fields and show how to approximate them. Then, we employ this basis to discretise shape Newton methods and investigate the impact of this discretisation on convergence rates.